2020
DOI: 10.3390/en13051235
|View full text |Cite
|
Sign up to set email alerts
|

Energy Utilization of Spent Coffee Grounds in the Form of Pellets

Abstract: Nowadays it is important to limit the use and combustion of fossil fuels such as oil and coal. There is a need to create environmentally acceptable projects that can reduce or even stop greenhouse gas emissions. In this article, we dealt with the objectives of energy policy with regard to environmental protection, waste utilization, and conservation of natural resources. The main objective of the research was to assess the possibility of the use of spent coffee grounds (SCG) as fuel. As a part of the solution,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 20 publications
0
22
0
1
Order By: Relevance
“…Many studies have investigated the pellet of coffee grounds and some have found slightly lower heating values (18.8 MJ/kg 50 , 19.6 MJ/kg 51 ) than that reported in this study while other report much higher heating values (23.4 MJ/kg 7 , 25.7 MJ/kg 52 ). Other studies have verified the pelletizing process through mixtures with other types of waste 53 or materials 54 , 55 , or with different percentages of moisture. Still others have modified other parameters such as die height, Lisowski et al (2019) 56 and have verified how the moisture of the matrix can be determined in the pelletizing process.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the pellet of coffee grounds and some have found slightly lower heating values (18.8 MJ/kg 50 , 19.6 MJ/kg 51 ) than that reported in this study while other report much higher heating values (23.4 MJ/kg 7 , 25.7 MJ/kg 52 ). Other studies have verified the pelletizing process through mixtures with other types of waste 53 or materials 54 , 55 , or with different percentages of moisture. Still others have modified other parameters such as die height, Lisowski et al (2019) 56 and have verified how the moisture of the matrix can be determined in the pelletizing process.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been conducted on the combustion performance and gaseous and particulate emission of SCG mixed pellets [5], evaluation of quality standards for pellets mixed with coffee and various biomasses [25], and determination of pellet characteristics according to pellet molding conditions [8]. Nosek et al, reported that the calorific value of pellets mixed with coffee grounds and pine sawdust increased with increasing in the proportion of coffee grounds and that the pellets with high proportions of coffee grounds produced increased the exhaust emissions [26]. However, there is a lack of evaluation based on the fuel quality standards to commercialize coffee and pine sawdust mixed pellets as fuel.…”
Section: Introductionmentioning
confidence: 99%
“…The reuse of these wastes is allowed to be valued, therefore, the coffee farms can take advantage of these resources [6]. The solid waste from the coffee agro-industry can be used for other purposes, for instance source of compost, substrate, biodiesel products and its by-products [7][8][9][10]. All these wastes obtained during the agro-industry process activity cause an adverse environmental impact if they are thrown into natural sources of water.…”
Section: Introductionmentioning
confidence: 99%